Implementação de aparato para medição de estado de polarização via formalismo de stokes-mueller - LIMA, Ruan Lucas Sousa (2024)
In this project, we present the setup and the implementation of a laboratory practice used to measure and analyze the polarization state of an arbitrary light beam. Backgrounded by the polarization Stokes parameters and Mueller matrices formalisms, it can be effectively implemented under the perspective of two main university principles: Teaching and Research. In the first, because this methodology yields a great resource for teaching more advanced concepts in optics; and in the second, since this technique, being expanded, may be applied in the spectroscopic investigation of phenomena regarding preferential directions; i.e., anisotropic phenomena. This work then establishes the very first step towards the analysis of this phenomenology in real samples of interest for the material science community, either through fluorescent emission or transmission analysis, both in solid (thin films) and liquids (solutions). For that, we prompted different polarization states using a homemade simulator, and then analyzed them according to the rotatable QuarterWave plate technique shown here. It says that the transmitted light signal through the wave plate followed by a linear polarizer is modulated as a harmonic superposition of a polarization state basis. In our experiments, we have created the basis states using other polarizers, and analyzed them at the wavelength in which the wave plate has retardance of a quarter wave (or 90º). With this procedure, we have shown the technique works correctly for the determination of the basis states, as well as for mixed states, where the experimental signal may be interpreted as a superposition of portions of that basis states. Finally, we have looked over the experimental results phenomenologically, so the physics of how the technique works could be clarified; given the theoretical background.